Dinamika Investasi Portofolio di Indonesia: Dampak Kebijakan Moneter dan Stabilitas Makroekonomi Tahun 2015–2025 - Bima Hardi; Anita Ramadona (CV. Kalimasada Group, 2026)
Portfolio investment is a crucial yet highly vulnerable source of external financing for emerging economies, with its movements being highly sensitive to macroeconomic conditions. This study analyzes the impact of the benchmark interest rate, the rupiah exchange rate, and inflation on portfolio investment in Indonesia during the 2015Q1–2025Q4 period using 44 quarterly observations sourced from Bank Indonesia. This research employs the Error Correction Model (ECM) approach to comprehensively examine both short-term and long-term dynamics. Estimation results prove that in both the long and short run, the interest rate has a significant positive effect on portfolio investment, while the exchange rate consistently exerts a highly significant negative impact. Conversely, inflation does not show a statistically significant effect in either the short or long run. The model also reveals an Error Correction Term (ECT) value of -0.941, indicating that 94.1% of capital flow disequilibrium is corrected very rapidly within a single quarter. These findings underscore that the combination of exchange rate stability and attractive interest rates is the most essential policy instrument in maintaining foreign investor confidence in Indonesia's financial markets.